Developing a holistic framework for assessing research impact in South African higher education institutions, using a research-intensive university as a case study - Mfengu, Andiswa (Department of Knowledge and Information Stewardship, 2025)
Scholarly communication has become less linear, less opaque and less rigid than before as both the research process and the end products are being transformed inexorably. The impact of research goes beyond academia, research also impacts society, and thus academic reward systems need to also be transformed to align with evolving research impact practices. The study sought to gather a complete view of research impact assessment practices, challenges and best practice for assessing research impact across disciplinary spaces at the University of Cape Town, the case study for this research, and based on these findings develop a holistic framework for the assessment of research impact to facilitate transformative and responsible research assessment for higher education institutions such as the University of Cape Town. The study was informed by the Payback Framework and New Institutional Theory. It adopted, within a pragmatist paradigm, an explanatory sequential mixed methods approach and data were collected using four instruments: an online questionnaire survey (255 academics, researchers and postdoctoral fellows); document analysis (six documents); semi-structured interviews (30 academics and researchers, and 10 key informants); and, bibliometric analysis (20 academics and researchers). Quantitative data were analysed using the Statistical Package for the Social Sciences (SPSS) while qualitative data were analysed thematically with NVivo. The study found that bibliometrics were the most used metric indicator for the 'Advancing knowledge' benefit category and academics and researchers surveyed seem satisfied with the use of bibliometrics to evidence this benefit category. Qualitative indicators were regarded more appropriate for evidencing other impacts beyond academia. Bibliometrics and 'Advancing knowledge' benefit category were also prioritised by the institution (UCT) and funders. Behavioural impact and bias were some of the main challenges with metric indicators that the surveyed academics and researchers highlighted; 'Responsible research practices' and 'Open science' were seen as being important principles for metrics use. Interview participants found that a meaningful approach for assessing research impact should be flexible, broad and context-sensitive. A case study technique (combination of qualitative and quantitative methods) and impact narratives were found to be the best approach for assessing research impact across disciplines in higher education. Institutional culture and structures were found to influence academics and researchers in 'not productive' ways as study participants found rules and structures to be limiting rather than providing an enabling environment for contributing to the discipline and society. Institutional transformation agenda and how academics and researchers are assessed were found to be misaligned. Lastly, extensive consultation and engagement with various stakeholders in the research community was found to be imperative to the process for the development of a holistic framework for assessing research impact. The study makes contributions to theory, practice and policy formulation. The proposed framework integrates the logic model, process-view approach and institutional context in assessing research impact. Research impact assessment is complex and multi-dimensional necessitating flexibility, contextualisation and working together. Higher education institutions and funders need to expand the range of academic activities they incentivise and reward; and thus move towards a less limited set of research impact assessment practices. Institutions and funders need to align policy and practice related to research impact assessment as any fundamental change necessitates a shift in policies, processes and structures for the new changes to be adopted and institutionalised. Lastly, a holistic and meaningful research impact assessment framework needs to be balanced, broad and responsible, and should align decisionmaking to the strategic mission and goals of the institution and funder